KNOWLEDGE SHARING REQUIREMENTS TO IMPROVE THE QUALITY OF THE AUDIT WORKS IN THE FEDERAL BOARD OF SUPREME AUDIT OF IRAQ - طه عبد الرحمن مصطفى; محسن وسام ياسين (Journal of Economics and Administrative Sciences, 2015)
The research studies the main variables for the concept of sharing in knowledge in one of the most important control agencies in Iraq, which is (The Federal Board of Supreme Audit). Also, the quality of the controlling businesses by the Board in light of the major challenges that facing the fight against signs of cheating and administrative and financial corruption for offices submitted to controlled and auditing, with the increasing and intensification of these appearances. In order to enable the Board to cope with this situation, has to be thinking hard about how to achieve excellence, progress and development to face these situations, through the application of sharing in knowledge for the financial controller, and then achieve the goals and objectives of the Board. The research aims to identify a very important aspect, which is sharing in knowledge and information between workers. In addition, analysis of the relationship between sharing in knowledge and its impact on the performance of the team and quality control work in control bodies, especially the Federal Board of Supreme Audit, since the research sheds light on a sample taken from it. The research includes two major hypotheses, the first for correlation relationships and the second for effect relationships between the research variables. The sample of research was selected from employees at the headquarters of The Federal Board of Supreme Audit totaling (63) employees, represented by (experts, managers of departments, heads of bodies, Deputy Chairman of the Commission). The research depend on a questionnaire included (37) items, by using personal interviews, field observations, and official documents, as assistant tools to perform it. The research adopted many statistical methods such as (arithmetic mean, standard deviation, variation coefficient, Spearman coefficient, and linear regression coefficient), where the results extracted by using (SPSS). The research has reached some results. The most important is the existence of correlation relationships between knowledge sharing and quality of control businesses. The research concluded some suggestions. The most important are enabling suitable and supportive environment that realize the importance of sharing in knowledge and the quality of control businesses, and the formulation of plans and programs to activate these two processes at the level of the organization and its control bodies, and the spreading and developing of a culture of sharing in knowledge.